Chrysis pseudobrevitarsis Linsenmaier 1951 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
55. Chrysis pseudobrevitarsis Linsenmaier, 1951 Chrysis ignita var. pseudobrevitarsis Linsenmaier 1951: 79. Lectotype ♀ (designated by Linsenmaier 1959: 158); Switzerland: Wallis (NMLS) (examined). Hellén 1952: 180. Chrysis pseudobrevitarsis : Valkeila 1962: 64, Erlandsson 1971: 88, Tumšs 1976: 22, Silfverberg 1981: 61, Vikberg 1986b: 68, Hedström 1989: 154, Nilsson 1991: 82, Soon 2004: 23, 46, Hallin 2009: 10, Johansson 2009, Allearter.dk 2010, Johansson 2010: 118, Orlovskytė et al. 2010: 151, Paukkunen 2010: 538, Smissen 2010d: 393, Johansson 2011: 35, Sjödin 2011, Soon & Saarma 2011: 15, Franzén et al. 2012: 27, Hallin 2012, Ranta 2012: 33, Rosa & Soon 2012, Dyntaxa 2013, Soon et al. 2014: 312–313. Chrysis mediadentata [part.]: Söderman & Vikberg 2003: 45, Material examined. Denmark. B : Almindingen, 17.VI.1964, 1 ♂; NEZ : Tisvilde Hegn, 25.VI.1975, 1 ♀ (Lomholdt). Norway: VAY: Farsund, Kviljo, 4.VII–4.VIII.2008, 1 ♀ (F. Ødegaard). Russian Fennoscandia (total 31 exx.): Ik : Terijoki [= Zelenogorsk]; Äyräpää [= Baryshevo]; Ka : Antrea [= Kamennogorsk]; Jääski [= Lesogorskiy]; Seiskari [= Ostrov Seskar]; Viipuri [= Vyborg]; Kl : Kurkijoki; Sortavala. Distribution. Denmark, Estonia, Finland, Latvia, Lithuania, Norway, Sweden, Russian Fennoscandia.—Transpalearctic: from West Europe to Mongolia (Linsenmaier 1997). Remarks. The species is known from all the Nordic and Baltic countries, but it is usually uncommon and found in low numbers. The northernmost records are from northern Sweden. In Finland it has declined and has been classified as near threatened (Paukkunen 2010). Soon (2004: 46) reported C. pseudobrevitarsis from Norway and Denmark, but later the record from Norway proved to be erroneous. However, one specimen was recently found from southern Norway (Farsund) and the determination was confirmed by DNA barcoding. Records from Denmark are based on two specimens in ZMUC, which were collected from Bornholm and Zealand (see data above). According to mitochondrial DNA studies, the species is ...